Microsatellite Instability in Mouse Models of Colorectal Cancer - Nicola Currey; Joseph J. Daniel; Dessislava N. Mladenova; Jane E. Dahlstrom; Maija R. J. Kohonen-Corish (Canadian Journal of Gastroenterology and Hepatology)
Microsatellite instability (MSI) is caused by DNA mismatch repair deficiency and is an important prognostic and predictive biomarker in colorectal cancer but relatively few studies have exploited mouse models in the study of its clinical utility. Furthermore, most previous studies have looked at MSI in the small intestine rather than the colon of mismatch repair deficient Msh2-knockout (KO) mice. Here we compared Msh2-KO, p53-KO, and wild type (WT) mice that were treated with the carcinogen azoxymethane (AOM) and the nonsteroidal anti-inflammatory drug sulindac or received no treatment. The induced tumors and normal tissue specimens from the colon were analysed with a panel of five mononucleotide repeat markers. MSI was detected throughout the normal colon in untreated Msh2-KO mice and this involved contraction of the repeat sequences compared to WT. The markers with longer mononucleotide repeats (37–59) were the most sensitive for MSI while the markers with shorter repeats (24) showed only minor change. AOM exposure caused further contraction of the Bat37 and Bat59 repeats in the distal colon of Msh2-KO mice which was reversed by sulindac. Thus AOM-induced carcinogenesis is associated with increased instability of mononucleotide repeats in the colon of Msh2-KO mice but not in WT or p53-KO mice. Chemoprevention of these tumors by sulindac treatment reversed or prevented the increased MSI.